Bottom-Up Planning and the Future of Planning Education in India - Angelique Chettiparamb (Journal of Planning Education and Research 2006; 26; 185, 2006)
The article discusses normative guidelines for reorienting planning education in India within the context of the immensely influential Constitutional Amendment Act of 1993. First, it briefly sketches the status of planning education at present in India, in relation to the role of planners in planning practice. It then descibes the changes that have taken place in general, following the Constitutional Amendment Act, dwelling more on the specific changes within the State of Kerala. The implications of these for planning education in general are then discussed normatively, highlighting three areas that need immediate attention from the planning academic community.